New Five Year Plan (1978-83) Health Draft Annual Plan 1978-79 - Government of Andaman and Nicobar (Government of Andaman and Nicobar Islands, 1977)
The New Five-Year Plan (1978-83) for the Andaman and Nicobar Islands focuses on strengthening healthcare services for rural and tribal populations across the Union Territory’s 352 islands. Recognizing geographic isolation and limited inter-island connectivity, the plan aims to establish seven new health schemes, upgrade Primary Health Centres (PHCs) across five blocks, and enhance referral services. Key initiatives include new PHCs in Arong and Katchal, filaria treatment clinics, the establishment of a Health Institute at Port Blair for training health personnel, and ongoing health education programs. With a total outlay of Rs. 266.171 Lakhs, including Rs. 51.035 Lakhs for tribal welfare, the plan emphasizes infrastructure, medical supplies, staffing, and training. By integrating preventive, curative, and educational strategies, the plan seeks to reduce health disparities, improve accessibility, and ensure sustainable health outcomes for the islands’ diverse population.
Andaman and Nicobar Administration
Andaman and Nicobar Administration
Keywords: Andaman and Nicobar Islands; Health Sector; State Plan; Rural Health; Tribal Health; Primary Health Centres; Filaria Treatment; Health Infrastructure; Health Education; Medical Training; Health Services Accessibility; Government Expenditure